Acute Kidney Injury in ADPKD Patients with Pneumonia. (25th July 2011) - Franco Palacios, Carlos; Keddis, Mira T.; Qin, Dingxin; Zand, Ladan; Li, Guangxi; Wang, Xiangling; Cartin-Ceba, Rodrigo; Hartman, Robert P.; Qian, Qi
Abstract : Background . In animal models, polycystic kidneys are susceptible to acute kidney injury (AKI). We examined the occurrence of AKI in a cohort of autosomal dominant polycystic kidney disease (ADPKD) and non-ADPKD patients with acute pneumonia. Design . All ADPKD patients admitted to Mayo Clinic Rochester for pneumonia from January 1990 to April 2010 were examined. Sixty-three patients had lobar infiltration and consolidation on chest X-ray. After excluding patients on dialysis, with organ transplantation, and on chronic immunosuppression, 24 remaining ADPKD patients were enrolled. Twenty-three of the 24 were matched with 92 (1 : 4 ratio) non-ADPKD pneumonia patients based on their baseline eGFR. AKI was defined as serum creatinine elevation ≥0.3 mg/dL. Results . Sixteen of the 23 ADPKD patients (69.6%) and 36 of the 92 (39.1%) non-ADPKD patients developed AKI, P = 0.008 . In both groups, those who developed AKI had a lower baseline eGFR (41.1 ± 5.00 versus58.7 ± 11.8 in ADPKD and40.2 ± 3.65 versus51.8 ± 2.24  mL/min/1.73 m 2 in the non-ADPKD group), more intensive care unit admissions, and longer hospital stays. AKI was associated with a reduced survival in both groups. Conclusions . Patients with ADPKD admitted for acute pneumonia had more frequent episodes of AKI than non-ADPKD patients with comparable kidney function.